Great Walls from Mao to Now: A Biographical Perspective on Adult Education Inside Chinese Communist Revolution - Roger Boshier; Xu Minghui (Adult Education Research Conference, 2011)
From 1921 onwards, adult education was a vital corollary of Chinese Communist revolution. In 1954 Yao Zhongda lived near Mao in the Zhongnanhai and became Chief of the Bureau of Workers’ and Peasants Education. He is now 86 years old. The purpose of this study was to capture his biography and reflect on what it means for 21st century China. Data was secured during a 10-day Beijing interview session. Yao is an outstanding figure in Chinese adult education and today’s scholar-officials could learn a lot from him.
Keywords: Chinese communism; revolutionary adult education; biography